The Use of the Everyone is Teacher here Learning Strategy in Affecting Class X SMA Students' Mathematical Critical Thinking Ability - Buang Saryantono; Joko Sutrisno AB; Hesti Noviyana (International Journal of Educational Research Excellence (IJERE), 2023)
The ability to think critically mathematically is one of the important abilities required in learning mathematics at the senior high school level in the independent curriculum. This ability is also one of the abilities demanded by the 21st century educational revolution. The importance of this ability is not in line with the mathematical critical thinking abilities of high school students, as was the problem of research in class X MIA at SMA Negeri 1 Natar Lampung Selatan. Given the importance of critical thinking skills, the purpose of this study was to determine the effect of using Everyone is a Teacher Here strategy on students' mathematical critical thinking abilities. This research is a quasi-experimental study with a population of all students of class X MIA even semester of SMA Negeri 1 Natar Lampung Selatan consisting of 8 classes with a total of 228 students, while 2 classes were taken, namely class X MIA 8 as the experimental class totaling 36, and class X MIA 7 as the control class, totaling 36. The sample was taken using a random sampling technique. Students' mathematical critical thinking ability is measured by a test in the form of a description of 5 questions which have previously been tested for validity and reliability. Testing the hypothesis in this study using the t test. From the results of hypothesis testing, it can be concluded that the use of the Everyone is a Teacher Here strategy can influence the mathematical critical thinking skills of class X MIA students at SMA Negeri 1 Natar Lampung.